Efektifitas Peer Education dengan Metode Ceramah Terhadap Pengetahuan SADARI Pada Remaja Di Puskesmas Kalitanjung Kota Cirebon Tahun 2024 - Wahyuni, Lily; Susan, Yanti (LPPM ITEKES Mahardika, 2025)
Background: The high incidence of breast cancer and tumors underscores the importance of early detection methods, one of which is Breast Self-Examination (SADARI). Increasing adolescents’ awareness and knowledge of SADARI is crucial for promoting preventive health behavior from an early age. Objective: This study aims to evaluate the effectiveness of peer education using the lecture method on adolescents’ knowledge of SADARI at the Kalitanjung Public Health Center, Cirebon City, in 2024. Methods: This research employed a quantitative approach with a quasi-experimental design, specifically a pretest-posttest design. The data were collected using a structured questionnaire and analyzed through paired sample t-tests. Both univariate and bivariate analyses were conducted to interpret the results. Results: The peer group education method led to 35 participants (100%) reaching the “skilled” category, while the lecture method resulted in 31 participants (88.57%) achieving the same. Statistical analysis revealed a significance value of 0.000 (p < 0.05), indicating a significant improvement in knowledge after the interventions. Furthermore, the peer education group had a higher mean posttest score (25.49) compared to the lecture group (23.07). The difference between the two methods was statistically significant, with a p-value of 0.005 (< 0.05). Conclusion: Peer education using the lecture method significantly improves adolescents’ knowledge of SADARI. Moreover, peer education demonstrates greater effectiveness than the conventional lecture method in enhancing understanding and awareness.